Laws and Environmental Protection in the Case of Fine Dust Particles not Exceeding 2.5 Microns - Chanthai, Methaporn; Atsawalapsakun, Waraporn; Atsawalapsakun, Chot; Kumansing, Santiphong (Sripatum Review of Humanities and Social Sciences, 2026)
The problem of fine particulate matter of less than 2.5 microns (PM 2.5) is an environmental crisis that has severely impacted the health, economy, and environment of Thailand, particularly in urban areas and the northern region, which are affected by open burning activities, forest fires, and heavy traffic. This article aims to analyze the role of Thai law in controlling PM 2.5 by studying the development of environmental legal principles, including key principles such as the precautionary principle, the polluter-pays principle, the principle of sustainable development, and the principle of public participation. Although Thailand has several relevant laws, such as the Environmental Quality Promotion and Conservation Act B.E. 2535 (1992), the Public Health Act B.E. 2535 (1992), and the Factory Act B.E. 2535 (1992), there is still a lack of specific laws on PM 2.5 and there are limitations in enforcement, such as duplication of authority, outdated air quality standards, and weak participatory mechanisms. This article proposes legislative and policy reforms, such as enacting specific laws on PM 2.5, increasing penalties, strengthening the role of citizens, and using technology to monitor pollution, to ensure effective, sustainable, and constitutionally aligned management of PM 2.5.